Empowering Adolescent Boys – Peer Education and Road Safety in Rural Maharashtra - Shwetangi Ravindra Shinde; Sagar Arvind Padhye; Nived G. Sudarson; Sujata R. Lavangare; Vijaykumar S. Singh (Indian Journal of Public Health, 2025)
Road accidents are a leading cause of death, morbidity, and economic burden among young individuals. This study aims to evaluate how effective a peer education program is in improving road safety knowledge, attitudes and practices among adolescent boys aged 16–19 from two villages. In Village “A,” 110 boys completed a baseline survey, and 10 were chosen as peer educators to provide the intervention. Village “B” served as the control group, receiving traditional road safety education. After 6 months, all participants took a post-test survey. The intervention group showed a significant increase in road safety knowledge compared to the control group (P < 0.0001), but there was no significant difference in attitudes (P = 0.34) or practices (P = 0.72). The study indicates that peer education can effectively enhance road safety knowledge, but further research is needed to see if it leads to lasting behavioural changes.